The fit of all-ceramic crowns cemented with different luting agents. - (:unkn) unknown (My University, 1992)
In this article the fit of all-ceramic crowns, cemented with different luting agents (zinc phosphate and resin cements), was investigated using a scanning electron microscope. The marginal opening of all-ceramic crowns cemented with zinc phosphate cement was 111.9 +/- 40.6 microns which was significantly greater than the 46.7 +/- 12.9 microns marginal opening of Cerestore crowns cemented with resin cement. Total film thicknesses of the cements were not uniform and there were certain discrepancies from margins to walls and to tip due to the die spacer.